(untitled) (Publicatio UEPG: Ciências Sociais Aplicadas, 2022)
ABSTRACT: This study is proposed in view of the immediacy to dialogue on the racial issue, with the aim of fostering the debate on the racial inequalities intensification in the Brazillian society in times of sanitary crisis. The epidemic does not only reflect in the public health system, it also denounces an unequal society’s effects concerning the most vulnerables of the population. The analysis carried out from this bibliographic research recovers the social determinants, which are fundamental instruments to impose on the black population the experience of a subordination situation. Furthermore to the COVID-19 disease effects in the human bodies, the debate is tensioned in the sphere of the epidemic effects in a society profoundly unequal and structurally racist, as is the case of the brazillian society. KEYWORDS: Racism; Social Inequalities; Pandemic